2016
DOI: 10.1111/jam.13081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel marine probiotic, Lactobacillus plantarum AH 78, on growth performance and immune response of Nile tilapia (Oreochromis niloticus )

Abstract: Marine Lact. plantarum AH 78 could be considered as a potential probiotic to control disease outbreaks in farmed Nile tilapia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 50 publications
4
47
0
Order By: Relevance
“…The expression of these genes was significantly up‐regulated in the liver of Nile tilapia fed SO‐1 diets compared to the control group ( p < 0.05). These findings are in agreement with the results of Liu et al (), Makled et al (), Hamdan et al (), who found that supplemental probiotic bacteria improved the abundance of pro‐inflammatory cytokines in tilapia. Similarly, probiotics up‐regulated pro‐inflammatory cytokine expression in rainbow trout (Peddie et al, ), zebrafish (Hsieh, Pan, & Chen, ) and koi carp (He et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The expression of these genes was significantly up‐regulated in the liver of Nile tilapia fed SO‐1 diets compared to the control group ( p < 0.05). These findings are in agreement with the results of Liu et al (), Makled et al (), Hamdan et al (), who found that supplemental probiotic bacteria improved the abundance of pro‐inflammatory cytokines in tilapia. Similarly, probiotics up‐regulated pro‐inflammatory cytokine expression in rainbow trout (Peddie et al, ), zebrafish (Hsieh, Pan, & Chen, ) and koi carp (He et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…At the end of the 50‐day probiotic feeding trial, fish were dissected under aseptic conditions. Liver tissue showed the most severe morphological changes and was selected for cytokine expression analyses as reported by Hamdan et al () and Zheng et al (). Subsequently, liver samples were aseptically removed from two fish collected randomly from each aquarium and stored at −80°C (Perez‐Sanchez et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different growth parameters as mean weight, % weight gain, % survival, food conversion ratio (FCR) and specific growth rate (SGR) were calculated using the following formulae (Hamdan, El‐Sayed, & Mahmoud, ; Liu et al, ).Meanweight=TotalweightTotalnumberoffishesWeightgain%=Finalmeanweight-InitialmeanweightInitialmeanweight×100%Survival=NumberoffishsurvivedNumberoffishstocked×100FoodconversionratioFCR=FeedgivennormalgWeightgainnormalgSpecificgrowthrateSGR%=lnWf-lnWiNo.ofdays×100Wf=Finalmeanweight,...…”
Section: Methodsmentioning
confidence: 99%
“…β-actin was used as a housekeeping control. The primer sequences for amplification of IL-10 and β-actin were as follows: (F, 5′-ACGACCCTGCTCACGTTATG-3; R, 5′-TCCGGGATGGAGTAAGAGGG-3′) and (F, 5′-GGTCGCCCAAGACATCAG-3; R, 5′-GCATACAGGGACAACACA-3′) (Hamdan et al, 2016), respectively. The relative expression of IL-10 in gut tissue samples was normalized to the expression of β−actin.…”
Section: Methodsmentioning
confidence: 99%